Biopolitics of the Zombie Corpses: Collectivity, Contagion, and Alterity - Onur Kartal (Problemos)
Inasmuch as the society is considered as a body today, social problems should be defined accordingly, as problems of hygiene and cleanliness. In this regard, various representations of zombie corpses in zombie movies can be conceived as concrete examples of threat and a perception of disease. In this article, I claim that the zombie figures in cinema bear a positive potential for the social life of humanity, and I will define this potential as a new opportunity for meeting the absolute alterity. Within this context, I analyse 28 Weeks Later and The World War Z and The Girl with All the Gifts to put forth the idea that what enables emancipation of humanity is contagion and alterity. Rather than destroying the capitalist rationalization without offering any alternatives, zombie corpses enounce the birth of a new form of social life as analysed through Pride and Prejudice and Zombies.